THE STRATEGIC ROLE OF DEFENSE EDUCATION IN STRENGTHIENING INDONESIA’S NATIONAL SECURITY SYSTEM - Muhamad Tarom (JURNAL PENDIDIKAN DAN PELATIHAN PERTAHANAN, 2025)
Defense education plays a strategic role in shaping a strong national defense posture that is responsive to military and non-military threats. This article examines the vital role of defense education in strengthening Indonesia's national security system amidst the ever-evolving global and regional dynamics. Using a qualitative descriptive approach, this study highlights the contribution of defense education in increasing national defense awareness, strengthening national identity, and fostering synergy between civilian and military components within the framework of national resilience. In the era of information disruption and multidimensional threats, defense education is the main foundation for building collective community awareness against ideological infiltration, foreign propaganda, and increasingly complex cyber threats. The research findings show that defense education integrated into the national education system functions as a strategic instrument to instill national values, patriotism, and national preparedness from an early age. Therefore, optimizing the curriculum, improving the quality of training, and expanding the scope of defense education programs are the main keys to building an adaptive and sustainable national security ecosystem. In addition, the importance of innovation in teaching methods, utilization of digital technology, and active involvement of civil society are supporting factors in expanding the reach and effectiveness of defense education. This study concludes that defense education is not merely an institutional need, but rather a long-term strategic investment for Indonesia's stability, sovereignty, and national resilience in the future.